Balinese Dogs: From Hero of the temple to dinner on the table - Ida Ayu Yuni Prasasti (Bali Tourism Board, 2017)
Bali is known as the islands of 1000 temples, Bali has a fascinating history about dogs. It is stated in the Mahaprasthanika Parva (Book of the Great Journey) on Mahabharata Story, after the end of the big war at Kurukshetra, Dharmawangsa (Yudistira) without any hesitation said that he would not go to heaven without his dog. He chose to suffer in the mortal world with his dog because the dog accompanied him throughout the journey. The journey of Yudhishthira to heaven accompanied by a dog, then inspires the Hindu Balinese people, in honor of the dog as a symbol of loyalty. No wonder, Balinese treat dog not as a pet but as a loyal friend. However, Animals Australia investigation team' member under pseudonym ‘Luke’ on his interview conducted by Australian Broadcasting Corp (ABC), claimed to have done a veiled investigation to uncover the practice of dog meat trade for consumption on the island of Bali. The man conducted a four-month investigation on the island, armed with small video cameras and mobile phones; he managed to document the activities of dog trading; ranging from how to catch the dog to how the meat is traded. Regarding the case, Government of Bali mentioned there is no such thing has been done in Bali. However, on several occasion, the dog is indeed used as a part of the ceremony. In the same time, the government also investigated the disseminated issue. However, they found nothing.